Disparitas Hukuman dalam Perkara Pidana Pencurian dengan Pemberatan Putusan Nomor. 782/PID.B/2019/PN.Smg dan Putusan Nomor. 157/PID.B/2019/PN.Smg - Novia, Mia; Santi; Setyaningsih (JURNAL RUANG HUKUM, 2024)
This research discusses disparities in judges' decisions regarding criminal acts of theft at the Semarang District Court, focusing on Decisions Number.782/PID.B/2019/PN.SMG and Number.157/PID.B/2019/PN.SMG. Judges, in determining punishment, not only follow legal provisions, but also consider human values, the principle of expediency, the effectiveness of punishment, and changes in the perpetrator's behavior. This research uses normative legal research methods with a comparative and case approach. Disparities were found in sentencing, especially in the duration of prison sentences. Judges tend to sentence with imprisonment rather than fines, in accordance with Article 363 paragraph (1) 4th of the Criminal Code. Factors causing disparities involve legal rules, judge's considerations, the amount of loss, and other influencing factors.